2016
DOI: 10.1111/asj.12651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chickpea husk dietary supplementation on blood and cecal parameters in rats

Abstract: Chickpea husk was functionally evaluated for antioxidant status, blood parameters, cecal fermentation and microbial profiles in rats. Fifteen male rats (5 weeks of age) were divided into three groups; they were individually housed and fed one of the following diets for 3 weeks: purified diet containing 5% cellulose (Cellulose), an identical diet in which cellulose was replaced by corn starch (Starch) or by chickpea husk (Chick). Rats were sacrificed to obtain blood and cecal digesta samples. Chickpea husk cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…After incubation, samples were analyzed for pH, short chain fatty acids (SCFA), lactate, ammonia, indole and skatole as previously reported (Myint et al . ). The remaining samples were frozen at −80°C for microbial analyses.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…After incubation, samples were analyzed for pH, short chain fatty acids (SCFA), lactate, ammonia, indole and skatole as previously reported (Myint et al . ). The remaining samples were frozen at −80°C for microbial analyses.…”
Section: Methodsmentioning
confidence: 97%
“…Determinations of total polyphenols, total flavonoids and total tannin were performed as previously reported (Myint et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Rats fed chickpea husk at 5% level showed an altered hindgut bacterial community based on different DGGE banding patterns [49]. The authors also found that chickpea husk extract exhibited anti-oxidative activity measured as free radical scavenging activity and lipid peroxidation.…”
Section: Backgroundsmentioning
confidence: 99%
“…The authors also found that chickpea husk extract exhibited anti-oxidative activity measured as free radical scavenging activity and lipid peroxidation. In fact, rats fed chickpea husk had lower thiobarbituric acid reactive substance (TBARS) values in their blood plasma, suggesting the potency of this byproduct as a health-promoting agent in animals [49]. These favorable effects of chickpea husk are considered to be due to the presence of tannins that could have different impact depending on molecular species ( i.e.…”
Section: Backgroundsmentioning
confidence: 99%